Pemeriksaan Telur Cacing Soil Transmitted Helminth (STH) pada Feses Pengrajin Batu Bata Di Kampung Jawa-Kota Batam - Rosi Esa Gustina; Nurfajrina Nurfajrina (Universitas Pahlawan Tuanku Tambusai, 2021)
Kampung Jawa Tanjung Piayu is one of the areas in the Riau Archipelago where some residents work as brick craftsmen. In the process of making bricks, craftsmen are in direct contact with the ground and do not wear personal protective equipment (PPE), making it possible to be infected with worms. The soil conditions used by brick craftsmen in Kampung Jawa Tanjung Piayu are moist soil, yellow in color, adjacent to puddles of water, lots of livestock swimming and passing around the excavation. These conditions will be very supportive for the development of STH worm eggs. This service aims to determine the results of the examination of STH worm eggs in the feces of brick craftsmen in Kampung Jawa, Batam City. The examination method used is the Native or Direct method, on 20 stool samples. The results of the examination showed that 20 (100%) of the stool samples examined were negative for STH worm eggs, which means that no STH worm eggs were found in the examined feces. One of the efforts to prevent further infection from STH is to perform early detection of STH infection, one method that can be done, namely through examination of feces on people who are at risk of worms.